Storyworlds: the elephant that forgot - Rayner, Shoo (HEINEMANN UK, 1998)
an elephant with a mind once sharp as the jungle's tallest trees, suddenly forgot everything$1 (Bher herd, her path, her name. In her search for lost memories, a glowing flower whispered, "To remember, you must forget what you thought you knew."s